2-D Resistivity, Magnetic And Gpr Signature Towards Human Burials Affected By Temporal Variation And Type Of Soil - Mansor, Muhamad Hafizuddin Mohd (2019)
In this study, 2-D resistivity, GPR and magnetic methods are used to detect human burials. Periods of burial (recent, intermediate and old) and type of soil in burial produced different anomaly signature. Besides, the decomposition of human body will affect the geophysical signature. Four study area were selected which are Kampung Permatang Pasir Muslim cemetery (sandy soil) which located in Balik Pulau, Kampung Titi Teras Muslim cemetery (sandy clay soil) which is in Balik Pulau, Kampung Sungai Tokang (clayey soil) which located in Nibong Tebal and Kampung Permatang Tok Jaya (wet sand) which located in Kepala Batas. In this study, 2-D resistivity and Ground Penetrating Radar (GPR) are used for 2-D and 3-D data subsurface imaging. While for ground magnetic survey, analytic signal and Euler deconvolution technique are used. This study aims to investigate the geophysical response of human burials towards the periods of burial and different types of soil.